2021
DOI: 10.3390/ijms23010337
|View full text |Cite
|
Sign up to set email alerts
|

The Plasminogen–Activator Plasmin System in Physiological and Pathophysiological Angiogenesis

Abstract: Angiogenesis is a process associated with the migration and proliferation of endothelial cells (EC) to form new blood vessels. It is involved in various physiological and pathophysiological conditions and is controlled by a wide range of proangiogenic and antiangiogenic molecules. The plasminogen activator–plasmin system plays a major role in the extracellular matrix remodeling process necessary for angiogenesis. Urokinase/tissue-type plasminogen activators (uPA/tPA) convert plasminogen into the active enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 137 publications
0
35
0
7
Order By: Relevance
“…La coexistencia de ictus isquémico agudo asociado a coartación de aorta es una rara ocurrencia en la población joven, (27,28,29), lo cual se manisfestó en el caso presentado.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La coexistencia de ictus isquémico agudo asociado a coartación de aorta es una rara ocurrencia en la población joven, (27,28,29), lo cual se manisfestó en el caso presentado.…”
Section: Discussionunclassified
“…La fibrinólisis intravenosa, es un procedimiento que constituye uno de los pilares fundamentales en el tratamiento del ictus isquémico agudo y se debe realizar en las primeras horas, desde el inicio de los síntomas, su funcion es facilitar la reperfusión endovascular y promover la disolución de los micro émbolos, mejorando la perfusión distal 9. Esto se logra activando el plasminógeno para que se transforme en plasmina, que es una enzima fibrinolítica que evita la formación de fibrina (10).…”
Section: Introductionunclassified
“…Upon binding to FPR1, the uPAR84-95 sequence or a shorter uPAR88-92 sequence corresponding to the synthetic, linear peptide Ser-Arg-Ser-Arg-Tyr (SRSRY), bind to FPR1, cause FPR1 internalization and trigger VnR activation with an inside-out type of mechanism, resulting in increased cell migration and angiogenesis [71,82]. It should be noted that uPAR controls angiogenesis either by focusing surface-associated proteolytic activity [85][86][87] or in an uPA-independent manner. Rao JS et al demonstrated that SuPAR released by cancer cells in the extracellular milieu may be recruited onto lipid rafts of umbilical vein endothelial cells (HVECs), thus, promoting Rac1-mediated endothelial cell migration and tumor angiogenesis [88].…”
Section: The Urokinase Plasminogen Activator Receptormentioning
confidence: 99%
“…An additional proteolytic enzyme whose synthesis is induced upon CD147 activation is the urokinase-type plasminogen activator (uPA) ( Table 2 ) [ 48 , 72 , 73 , 74 ]. The latter can straightly degrade the ECM [ 75 ] or convert latent plasminogen to active plasmin that, in turn, digests the ECM both directly and by activating MMPs ( Table 2 ) [ 76 ]. As with MMPs, the expression of uPA is also preceded by the activation of MAPK and/or AKT signaling, and can be induced by NF-kB, AP-1, Sp-1, or ETS transcription factors ( Figure 1 ) [ 77 , 78 , 79 , 80 ].…”
Section: Cd147 and Invasive Oscc Developmentmentioning
confidence: 99%